Distal spinal muscular atrophy with vocal cord paralysis. Issue 3 (March 1992) - Pridmore, C; Baraitser, M; Brett, E M; Harding, A E
Abstract : We describe a family with distal spinal muscular atrophy and vocal cord paralysis, similar to the condition reported by Young and Harper in 1980. Both pedigrees are consistent with autosomal dominant inheritance.